Literacy Education Using Android Pancasila Student Profile with Local Folklore in The Emancipated Learning Era - Suprapto; Laksono, Agus Edy (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2023)
The Profile of Pancasila Students in Permendikbud Number 22 of 2020 concerning the Ministry of Education and Culture Strategic Plan for 2020-2024 needs to be supported. The nation's culture has been written down from generation to generation and classically in local folklore, which contains good character values ​​under Pancasila. Various Indonesian local folklore is taught in secondary schools. Local Indonesian folklore should be put forward because it contains the dimensions of the Pancasila Student Profile. In addition, education adapts to technological developments. This study aimed to determine the feasibility of the android Pancasila Student Profile with local folklore in learning and to determine the literacy skills and dimensions of the Pancasila Student Profile owned by secondary school students in the emancipated era. It involves researchers from two different fields. This research supports the transformation of higher education. The research method is R&D inspired by the Joy and Bolitho model to produce products on a not-too-large scale. The flow chart uses the Tesmer design, including the preliminary stages, expert validation, and field/formative tests. This research produced an application product for Pancasila student profiles as a form of literacy education instilled through folklore. These findings and discussions are important because they are positive things for increasing student’s literacy.